Pengaruh Sarana Prasarana Sekolah dan Lingkungan Kerja Terhadap Kinerja Guru - Azhariah Rachman; Ella Andriyani; Petrus Jacob Pattiasina; Muwafiqus Shobri; Ismatul Izzah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
Teacher performance is an important thing that must be the attention of teachers and related parties, the good or bad of a teacher's performance will have an impact on the learning outcomes achieved by students. In this case, the teacher's performance must continue to be improved through supporting factors such as complete infrastructure so as to motivate teachers to be enthusiastic in carrying out learning and a conducive work environment so that teachers feel safe and comfortable in carrying out their duties. This research was conducted with the aim of knowing how the influence of school infrastructure and work environment on teacher performance. This study uses quantitative methods with the help of the IBM SPSS version 25 application, tested the validity and reliability of the research instrument, this research data uses primary data obtained from respondents. Respondents in this study were 74 respondents using random sampling method which took the entire population to be used as samples and data collection in this study using a questionnaire. The results of this study indicate that the variables of school infrastructure (X1) and work environment (X2) have an influence on teacher performance (Y).